BENTUK-BENTUK DUKUNGAN SOSIAL PADA PEGAWAI NEGERI SIPIL MENJELANG MASA PENSIUN - Sekarsari, Ni Kadek Widhi Dwi; Susilawati, Luh Kadek Pande Ary (Jurnal Psikologi Udayana; Vol 2 No 2 (2015), 2015)
Civil Servant (PNS) is part of the state apparatus that became one of the most important elements in the government. As a civil servant, people must be follow the rule included in Indonesian Regulation No. 43 Yr. 1999. Dismissal or retirement is one rule that applies to every member of civil servant. Dismissal or retirement of civil servants was a time when a person is laid off from a job appropriate age limits stipulated in Government Regulation (Dewi, 2011). Retirement would be associated with civil servant prepared or unprepared when entering that phase. Based on this, researchers are interested to see the preparations related to the readiness of civil servants towards retirement and social support necessary forms ahead of the retirement of civil servants.   This study used qualitative research methods with a phenomenological approach. Respondents in this study were four people whose status as civil servants in the province of Bali. Data collection techniques used in this study were interviews and observation.   The results of this study indicate that the civil servants who will retire requires good support from family, co-workers, as well as institutions. Support from family is the most important support is needed before the retirement of civil servants in the types of emotional support and information support. In addition, preparations are need of social support in the civil servants towards retirement include the preparation of financial, health or fitness, role adjustment, leisure time activities, as well as health insurance.     Keywords: civil servants, social support, retirement